Prenatal natural history of isolated fetal mild bilateral pyelectasis - Gustavo de Paula Pereira (Clinics)
OBJECTIVE: To analyze the prenatal outcomes in a cohort of fetuses with mild bilateral pyelectasis and determine whether performing serial ultrasounds is a good follow-up strategy. METHODS: A prospective longitudinal study was conducted on 62 fetuses with mild bilateral pyelectasis. Fetal mild bilateral pyelectasis was considered when the renal pelvis measured (in millimeters) ≥5.0 to 10.0, ≥7.0 to 10.0, and ≥10.0 to 15 at ≤23 weeks 6 days, 24 to 31 weeks 6 days, and ≥32 weeks, respectively, with no uretero-calyceal dilatation. Ultrasounds were performed every 3 weeks to assess whether the mild bilateral pyelectasis regressed, remained unchanged (Group 1) or progressed (Group 2). RESULTS: Group 1 consisted of 53 fetuses (85.4%), and progression was observed in 9 cases (Group 2, 14.6%). The initial renal pelvis diameter was significantly larger in fetuses with progression (p=0.028). Statistically significant differences in the renal pelvis diameter were also found at weeks 31 and 35 for both kidneys (p<0.05). The cases requiring intrauterine procedures or early delivery were not observed. CONCLUSION: Fetal mild bilateral pyelectasis with no calyceal dilatation is a benign condition that can be managed in the postnatal period. The initial renal pelvis diameter and the diameter in week 31 or 35 were valuable parameters for identifying cases that would eventually need specific postnatal procedures.